Prenatal, perinatal and postnatal factors associated with autism spectrum disorder - Imen Hadjkacem; Héla Ayadi; Mariem Turki; Sourour Yaich; Khaoula Khemekhem; Adel Walha; Leila Cherif; Yousr Moalla; Farhat Ghribi (Elsevier, 2016)
Objective: To identify prenatal, perinatal and postnatal risk factors in children with autism spectrum disorder (ASD) by comparing them to their siblings without autistic disorders. Method: The present study is cross sectional and comparative. It was conducted over a period of three months (July-September 2014). It included 101 children: 50 ASD's children diagnosed according to DSM-5 criteria and 51 unaffected siblings. The severity of ASD was assessed by the CARS. Results: Our study revealed a higher prevalence of prenatal, perinatal and postnatal factors in children with ASD in comparison with unaffected siblings. It showed also a significant association between perinatal and postnatal factors and ASD (respectively p = 0.03 and p = 0.042). In this group, perinatal factors were mainly as type of suffering acute fetal (26% of cases), long duration of delivery and prematurity (18% of cases for each factor), while postnatal factors were represented principally by respiratory infections (24%). As for parental factors, no correlation was found between advanced age of parents at the moment of the conception and ASD. Likewise, no correlation was observed between the severity of ASD and different factors. After logistic regression, the risk factors retained for autism in the final model were: male gender, prenatal urinary tract infection, acute fetal distress, difficult labor and respiratory infection. Conclusions: The present survey confirms the high prevalence of prenatal, perinatal and postnatal factors in children with ASD and suggests the intervention of some of these factors (acute fetal distress and difficult labor, among others), as determinant variables for the genesis of ASD. Resumo: Objetivo: Identificar fatores de risco pré-natal, perinatal e pós-natal em crianças com transtorno do espectro do autismo (TEA) ao compará-las a irmãos sem transtornos de autismo. Método: Este estudo é transversal e comparativo. Ele foi conduzido em um período de três meses (julho a setembro de 2014). Incluiu 101 crianças: 50 crianças com TEAs diagnosticadas de acordo com os critérios do DSM-5 e 51 irmãos não afetados. A gravidade do TEA foi avaliada pela Escala de Avaliação do Autismo na Infância (CARS). Resultados: Nosso estudo revelou uma prevalência maior de fatores pré-natais, perinatais e pós-natais em crianças com TEA em comparação a irmãos não afetados. Também mostrou uma associação significativa entre fatores perinatais e pós-natais e TEA (respectivamente p = 0,03 e p = 0,042). Nesse grupo, os fatores perinatais foram principalmente do tipo sofrimento fetal agudo (26% dos casos), longa duração do parto e prematuridade (18% dos casos em cada fator), ao passo que fatores pós-natais foram representados principalmente por infecções respiratórias (24%). No que diz respeito a fatores dos pais, nenhuma correlação foi encontrada entre a idade avançada dos pais no momento da concepção e o TEA. Da mesma forma, nenhuma correlação foi estabelecida entre a gravidade do TEA e fatores diferentes.Após regressão logística, os fatores de risco de autismo encontrados no modelo final foram: sexo masculino, infecção pré-natal do trato urinário, sofrimento fetal agudo, parto difícil e infecção respiratória. Conclusões: Esta pesquisa confirma a alta prevalência de fatores pré-natais, perinatais e pós-natais em crianças com TEA e sugere a intervenção de alguns desses fatores (sofrimento fetal agudo, parto difícil...) como variáveis determinantes para a gênese do TEA. Keywords: Autism spectrum disorder, Child, Risk factors, Prenatal, Perinatal, Postnatal, Palavras-chave: Transtorno do espectro do autismo, Criança, Fatores de risco, Pré-natal, Perinatal, Pós-natal